Investigating Product Involvement Issues for Mobile Phone Services: A Study of Filipino Mobile Phone Users - Capistrano, Erik Paolo (Philippine Management Review; Vol 20 (2013), 2013)
The mobile phone market in the Philippines is an interesting proposition.  While the very extensive usage of mobile phone communications has earned the country a reputation of being the “texting capital” of the world, the emergence of next generation mobile communication devices and communication technology platforms has yet to be fully understood.  This study aims to determine the particular levels of involvement Filipino mobile phone users place on such next generation mobile phone products and services.  This study compares the levels of involvement on five mobile phone services across two different demographic factors – regular mobile phone vs. smart phone users and postpaid vs. prepaid subscribers.  The study shows that being technologically more complex, smart phone users place higher levels of involvement on the services available through their devices.  The same is true with higher-priced items.  This implies that marketers and advertisers should seriously reconsider their allocation of resources to enable consumers to know and learn about mobile phone products and services with respect to the levels of involvement that users place on each one.